Application of Hyperthermia for Cancer Treatment: Synthesis and Characterization of Magnetic Nanoparticles and their internalization on Tumor Cell Lines - Chaparro, Catarina Isabel Parente (2020)
Cancer research is considered an increasingly logical science with great potential for the development of new treatment options. Advances in nanomedicine have resulted in rapid progress of nanomaterials development with considerable potential in cancer treatment. One alternative treatment option is the use of magnetic nanoparticles (mNPs) for the induction of intracellular hyperthermia. The theory behind hyperthermia is to kill cancer cells without the use of drugs (chemotherapy) or radiation (radiotherapy) just by increasing temperature in tumor site. This idea is based on higher sensitivity of cancer cells to temperature oscillations when compared to normal cells, therefore decreasing the side effects. In this dissertation project, the main objective is the internalization of magnetic nanoparticles in two types of breast cancer cell lines, where one of them express the cell-surface carbohydrate antigen sialyl-Tn (STn) which is not observed in normal healthy tissues. For these reasons, another purpose of this thesis project is the development of a complex monoclonal antibody-conjugated mNPs against sialyl Tn that will confer specificity to the whole system due its action in the specific target cells. In this context, we will have surface iron oxide nanoparticles and antibody-conjugated mNPs that will be used as heat producers under the application of an external magnetic field, leading to breast cancer cells death.